Effect of Chloroquine on Morphology of Cytoplasmic Granules in Maturing Human Leukocytes—an Ultrastructural Study - Fedorko, Martha (1967)
Bone marrow and peripheral blood from patients who had received chloroquine phosphate were studied to determine the effect of this drug on the ultrastructure of cytoplasmic granules in leukocytes. Neutrophils from approximately one-half of the patients who were treated developed abnormal cytoplasmic granules. Vacuolar, lamellar, and particulate components within abnormal, large granules were present in myelocytes from certain patients who received chloroquine therapy. Mature neutrophils and lymphocytes from these patients showed variable numbers of large, membrane-bounded structures containing myelin figures. Cytoplasmic granules in eosinophilic myelocytes from patients treated with chloroquine did not contain the usual crystalloid structure, but instead contained small whorls of osmiophilic material. The granules in abnormal mature eosinophils were replaced by large vacuoles which contained amorphous material. The abnormal granules seen in these various white cells after chloroquine therapy may either reflect defective granule formation or autophagy.